Chemical Investigation of Sansevieria zeylanica leaves. - GEETHA NAMBIAR, M.K.; MOHAMED SHAFI, P. (Asian Journal of Chemistry, 2010)
Chemical investigaion on the leaves of Sansevieria zeylanica has resulted in the isolation and identification of hentriacontane, tritriacontane, tetratriacontane, pentatriacontane, tetratriacontanol, dotriacontanol, triacontanol, nonacosanol and β-sitosterol. Two long chain esters have also been isolated and identified. In addition two cycloartan derivatives also were isolated but not fully characterised.